23-16n=-1

Simple and best practice solution for 23-16n=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23-16n=-1 equation:


Simplifying
23 + -16n = -1

Solving
23 + -16n = -1

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -16n = -1 + -23

Combine like terms: 23 + -23 = 0
0 + -16n = -1 + -23
-16n = -1 + -23

Combine like terms: -1 + -23 = -24
-16n = -24

Divide each side by '-16'.
n = 1.5

Simplifying
n = 1.5

See similar equations:

| 3m2/8=6 | | -7(6x+5)=-7x+14 | | 0=00m | | 1,340,000,000,000i=23 | | -15=-1.5m | | (2x-4y+6)dx=(3-x-y)dy | | 3tan^2x+4=5 | | (6)(3i+4)(1)+(4y+1)(2i)=(8iy+2i)+(18i+24) | | 19x+13y=7 | | -8x+4y=-12 | | 15-d=8 | | 0.045x-5/8y=120 | | x^8-26x+25=0 | | 2x+14i=1 | | (x^3+3x^2-16x-48)=0 | | -37+46.98-(-0.02)= | | 5s-(100+2s)=0 | | 3(10-6)(3-7)= | | 55m-139m-64m= | | 8x^6/6x^3 | | ln(x-3)=1.4 | | x-9(2/3x-6)=30 | | 1/2z=9/4 | | -5/13x=-8 | | 5m-139m-64m= | | 10m^3n^3-2mn^2+14mn= | | x+y-3z=-7 | | -9+8x=7x+15 | | 5(x+8)-6=44 | | 8x^2-28x+2x-7=.5 | | 5849=3.14x*81 | | 11w=132 |

Equations solver categories